Micro-nano hybrid SiCp reinforced aluminum matrix composite cylindrical part and preparation method thereof

By performing high-energy ball milling of micron SiCp, nano SiCp and aluminum powder, and high-temperature dissolution and ultrasonic treatment with aluminum alloy, combined with die casting, homogenization treatment, continuous forging, backextrusion and T6 heat treatment, the problems of poor mechanical properties, complicated processes and high cost in the existing aluminum-based composite cylinder preparation methods are solved, and the preparation of aluminum-based composite cylinder parts with excellent mechanical properties is achieved.

CN119501073AActive Publication Date: 2025-02-25NORTHWESTERN POLYTECHNICAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411555567.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing aluminum-based composite cylinder preparation methods have problems such as poor mechanical properties, complicated preparation processes and high costs.

Method used

Micron SiCp, nano SiCp and aluminum powder are mixed with high-energy ball milling, followed by high-temperature dissolution and ultrasonic treatment with aluminum alloy, followed by die-casting and homogenization treatment, and finally micro-nano hybrid SiCp-reinforced aluminum-based composite cylindrical parts are obtained through continuous forging, backextrusion and T6 heat treatment.

Benefits of technology

The mechanical properties of aluminum-based composite materials are improved, the uniform distribution of the reinforcement body in the aluminum alloy melt is achieved, cast defects are eliminated, and cylindrical parts with excellent mechanical properties are prepared, and the process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501073A_ABST
    Figure CN119501073A_ABST
Patent Text Reader

Abstract

The invention discloses a micro-nano hybrid SiCp reinforced aluminum matrix composite cylindrical part and a preparation method thereof, and belongs to the technical field of plastic processing of aluminum alloy materials. According to the preparation method provided by the invention, micron SiCp, nano SiCp and aluminum powder are mixed and then subjected to high-energy ball milling, the mixture and aluminum alloy are subjected to high-temperature dissolution and ultrasonic treatment, then die casting and homogenization treatment are carried out, and then continuous forging, backward extrusion and T6 heat treatment are carried out, so that the micro-nano mixed SiCp reinforced aluminum matrix composite cylindrical part is obtained. According to the micro-nano mixed SiCp reinforced aluminum matrix composite cylindrical part prepared through the preparation method, nanoscale SiCp and micron SiCp can be embedded with aluminum powder, the strength and hardness of crystals are improved, and then the mechanical property of an aluminum matrix composite is improved; by means of continuous forging and backward extrusion thermal deformation, as-cast defects such as shrinkage porosity and air holes can be eliminated, grain refinement is achieved, reinforcement distribution is improved, and therefore the cylindrical part is endowed with excellent mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aluminum alloy material processing technology, and in particular to a micro-nano hybrid SiC p Reinforced aluminum-based composite material cylindrical component and preparation method thereof. Background Art

[0002] Aluminum matrix composites (AMCs) have higher specific strength, specific stiffness, good high temperature stability, lower linear expansion coefficient and excellent wear resistance, and have broad application prospects in aerospace, automobile transportation, and electronic 3C fields. In order to further improve the mechanical properties of aluminum matrix composites, the addition of particle-reinforced metal matrix composites is usually used to effectively balance the contradiction between the strength and plasticity of traditional AMCs. Silicon carbide particles (SiC p ) has comprehensive properties such as high strength, high modulus, high hardness and low density, and is widely used as a reinforcement phase in various aluminum-based composites to improve the strength and modulus of aluminum-based composites. However, existing nano-scale SiC p The addition of materials, due to their large surface energy, is very easy to agglomerate. p The wettability with aluminum-based composite materials is poor and it is difficult to add into aluminum-based melt. Therefore, it is necessary to develop an optimized preparation process to prepare aluminum-based composite materials with excellent comprehensive performance and thus achieve the overall mechanical properties of the cylinder.

[0003] However, the existing preparation methods of cylinders made of aluminum-based composite materials have the following problems: first, only physical compounding is performed, which fails to affect the essence of the aluminum-based composite materials, thereby resulting in poor mechanical properties of the cylinders; second, the preparation process is complicated and costly, which is not conducive to large-scale production. Summary of the invention

[0004] The purpose of this application is to disclose a micro-nano hybrid SiC p Reinforced aluminum-based composite cylindrical parts and preparation methods thereof are intended to solve the existing problems based on micro-nano hybrid SiC p The preparation method of cylindrical parts made of reinforced aluminum-based composite materials has technical problems such as poor mechanical properties, complicated preparation process and high cost.

[0005] In order to achieve the above purpose, the technical solution of this application is:

[0006] The first aspect of the present application provides a micro-nano hybrid SiC p A method for preparing a reinforced aluminum-based composite material cylindrical member, the method comprising:

[0007] Micron SiC p 、Nano SiC p After mixing with aluminum powder, high-energy ball milling is performed to obtain SiC-Al composite particles;

[0008] The SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, and then die-cast and homogenized to obtain the cast SiC p Reinforced aluminum matrix composites;

[0009] The cast SiC p After the reinforced aluminum-based composite material is forged, reversely extruded and subjected to T6 heat treatment, the micro-nano hybrid SiC p Reinforced aluminum matrix composite cylindrical parts.

[0010] In combination with the first aspect, preferably, the micron SiC p The particle size is 0-5 μm, and the added mass fraction is 2.5 wt%.

[0011] In combination with the first aspect, preferably, the nano-SiC p The particle size is 0-50nm, and the added mass fraction is 1.5wt%.

[0012] In combination with the first aspect, preferably, the micron SiC p 、Nano SiC p The mass ratio to aluminum powder is 1:10.

[0013] In combination with the first aspect, preferably, the micron SiC p 、Nano SiC p When the high-energy ball milling treatment is carried out after mixing with aluminum powder, it is carried out in three stages. The first stage is at 150rpm for 4 hours, the second stage is at 220rpm for 10 hours, and the third stage is at 330rpm for 6 hours.

[0014] In combination with the first aspect, preferably, the aluminum alloy is an Al-Mg-Si alloy, and its mass fraction is 97.6% Al, 1.6% Mg, and 0.8% Si.

[0015] In combination with the first aspect, preferably, when the SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, the ultrasonic frequency is 20 kHz, the power is 3000 W, and the treatment time is 20 min.

[0016] In combination with the first aspect, preferably, after the SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, the die casting is performed at a temperature of 500° C., a pressure of 400 MPa, and a time of 3 min.

[0017] In combination with the first aspect, preferably, the cast SiC p When the reinforced aluminum matrix composite material is forged, the temperature is 400°C;

[0018] And / or, during the T6 heat treatment, the solution treatment is at 550° C. for 2 h, and the aging treatment is at 180° C. for 12 h.

[0019] The second aspect of the present application provides a micro-nano hybrid SiC prepared by the preparation method described in the first aspect. p Reinforced aluminum matrix composite cylindrical parts.

[0020] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0021] The preparation method provided by the application is to form a micron SiC p 、Nano SiC p After mixing with aluminum powder, high-energy ball milling is performed, and after die-casting with aluminum alloy, continuous forging, reverse extrusion and T6 heat treatment are performed to obtain micro-nano hybrid SiC p Reinforced aluminum matrix composite cylindrical parts. On the one hand, it can make nano-scale SiC p , Micron SiC p By intercalating with aluminum powder, the recrystallization degree of the composite material is improved, the strength and hardness of the crystal are increased through the grain boundary pinning effect, Orowan strengthening effect and promotion of nucleation mechanism. At the same time, it can achieve a density similar to that of the aluminum alloy matrix, thereby improving the mechanical properties of the aluminum-based composite material; on the other hand, it can simultaneously improve the wetting and dispersion of the SiC-Al composite particle reinforcement in the aluminum alloy molten matrix in a short time, and achieve its uniform distribution; thirdly, it can eliminate casting defects such as shrinkage and pores to achieve grain refinement, improve the distribution of reinforcements, and then prepare cylindrical parts with excellent mechanical properties. At the same time, the preparation process provided by this application is simple and easy to repeat, so that the strength and plasticity of the aluminum-based composite cylindrical parts are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The micro-nano hybrid SiC provided in the embodiment of the present application p Process flow chart for preparing reinforced aluminum matrix composite cylindrical parts;

[0024] Figure 2 A schematic diagram of an angled casting mold used in a die-casting process provided in an embodiment of the present application;

[0025] Figure 3 A schematic diagram of a continuous forging + reverse extrusion device provided in an embodiment of the present application;

[0026] Figure 4 A macroscopic photograph of SiC-Al composite particles provided in an embodiment of the present application;

[0027] Figure 5 The cast Al-1.6Mg-0.8Si, 5μm-4wt%SiC provided in the embodiment of the present application p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p / Scanning electron microscope image of Al-1.6Mg-0.8Si reinforced aluminum matrix composite;

[0028] Among them, (a) Al-1.6Mg-0.8Si; (b) 5μm-4wt%SiC p / Al-1.6Mg-0.8Si; (c) 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si; (d) (5μm-2.5wt%+50nm-1.5wt%)SiC p / Al-1.6Mg-0.8Si;

[0029] Figure 6 Al-1.6Mg-0.8Si, 5μm-4wt%SiC provided in the embodiment of the present application p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p / SEM image of Al-1.6Mg-0.8Si reinforced aluminum matrix composite cylindrical parts;

[0030] Among them, (a) Al-1.6Mg-0.8Si; (b) 5μm-4wt%SiC p / Al-1.6Mg-0.8Si; (c) 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si; (d) (5μm-2.5wt%+50nm-1.5wt%)SiC p / Al-1.6Mg-0.8Si;

[0031] Figure 7 The cast Al-1.6Mg-0.8Si, 5μm-4wt%SiC provided in the embodiment of the present application p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p / Stress-strain curve of Al-1.6Mg-0.8Si reinforced aluminum matrix composites;

[0032] Figure 8 Al-1.6Mg-0.8Si, 5μm-4wt%SiC provided in the embodiment of the present application p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p Stress-strain curve of / Al-1.6Mg-0.8Si reinforced aluminum matrix composite cylindrical parts. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0035] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0036] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] It should be noted that all raw materials and reagents in the examples of this application are purchased on the market or prepared according to conventional methods well known to those skilled in the art. p 、Nano SiC p The aluminum powder and the like are purchased from the market or prepared according to conventional methods well known to those skilled in the art.

[0039] In the first aspect, the present application embodiment provides a micro-nano hybrid SiC p A method for preparing a reinforced aluminum-based composite material cylindrical member, the method comprising:

[0040] Micron SiC p 、Nano SiC p After mixing with aluminum powder, high-energy ball milling is performed to obtain SiC-Al composite particles;

[0041] The SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, and then die-casted and homogenized to obtain the cast SiC p Reinforced aluminum matrix composites;

[0042] The cast SiC p After the reinforced aluminum matrix composite material is subjected to continuous forging, reverse extrusion and T6 heat treatment, the micro-nano hybrid SiC p Reinforced aluminum matrix composite cylindrical parts.

[0043] Among them, on the one hand, it can make nano-scale SiC p , Micron SiC pBy intercalating with aluminum powder, the recrystallization degree of the composite material is improved through the grain boundary pinning effect, Orowan strengthening effect and promotion of nucleation mechanism, and the strength and hardness of the crystal are increased, thereby improving the mechanical properties of the aluminum-based composite material; on the other hand, it can simultaneously improve the wetting and dispersion of the SiC-Al composite particle reinforcement in the aluminum alloy molten matrix in a very short time, and achieve its uniform distribution; thirdly, it can eliminate casting defects such as shrinkage and pores to achieve grain refinement, improve reinforcement distribution, and prepare cylindrical parts with excellent mechanical properties. At the same time, the preparation process of this application is simple and easy to repeat, which significantly improves the strength and plasticity of the aluminum-based composite cylindrical parts.

[0044] In the embodiment of the present application, the micron SiC p The particle size is preferably 0-5 μm, and the added mass fraction is preferably 2.5 wt%. p The particle size is 0-50nm, and the added mass fraction is preferably 1.5wt%, micron SiC p 、Nano SiC p The mass ratio of nano-SiC to aluminum powder is preferably 1:10. p Reinforcement, can pin the grain boundary, inhibit grain growth, and provide Orowan strengthening effect, while adding micron SiC p The degree of recrystallization of the aluminum matrix can be improved through the thermal mismatch strengthening mechanism and the particle stimulated nucleation mechanism. By controlling the addition amount of the two, the synergistic improvement of the strength and plasticity of aluminum-based composite cylindrical parts can be achieved.

[0045] In the embodiment of the present application, the micron SiC p 、Nano SiC p After mixing with aluminum powder, high-energy ball milling was carried out in three stages: the first stage was at 150rpm for 4 hours, the second stage was at 220rpm for 10 hours, and the third stage was at 330rpm for 6 hours. p The process of high-energy ball milling with aluminum powder is as follows: the first stage is material mixing (150rpm, 4h), the second stage is material embedding (220rpm, 10h), and the third stage is material welding (330rpm, 6h). Clockwise rotation and counterclockwise rotation are performed alternately every hour, with a rest period of 30min. p The mass ratio of aluminum powder to aluminum powder is 1:10, and high-energy ball milling is performed under argon protection atmosphere. Through this step, micro- and nano-SiC p Get effective dispersion, while SiC p The millimeter-sized SiC-Al composite particles are obtained by high-energy ball milling. pIf the mass ratio of aluminum powder to aluminum powder is lower than 1:10, it is difficult to ball-mill into millimeter-sized composite particles.

[0046] In the embodiment of the present application, the aluminum alloy is preferably an Al-Mg-Si alloy. The Al-Mg-Si alloy has good corrosion resistance and excellent machinability, but its strength and modulus are relatively low. SiC ceramic particles (SiC p ) has excellent properties such as high strength, high hardness, high wear resistance, oxidation resistance, high thermal conductivity, low thermal expansion rate, and is not corroded by most acid and alkali solutions. It is a good reinforcement phase. Based on this, the present application adopts Al-Mg-Si alloy as the base alloy, and by adding SiC p , improve the mechanical properties of Al-Mg-Si alloy and expand its application. Among them, the mass fraction of Al-Mg-Si alloy is preferably Al 97.6%, Mg 1.6%, Si 0.8%. Through the selection of this aluminum alloy, magnesium and silicon elements can form Mg2Si phase, which has a good strengthening effect in aluminum alloy. In addition, SiC p The introduction of reinforcement phase can improve the strength of the material on the one hand, and promote the precipitation of Mg2Si phase on the other hand. p The synergistic effect of the reinforcement phase and the Mg2Si phase can effectively improve the strength and hardness of the aluminum-based composite material.

[0047] In the embodiment of the present application, when the SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, the ultrasonic frequency is preferably 20kHz, the power is preferably 3000w, and the treatment time is preferably 20min. p It is evenly distributed in the aluminum melt, and ultrasonic treatment has a degassing effect.

[0048] In the embodiment of the present application, the cast SiC p When the reinforced aluminum-based composite material is continuously forged, the temperature is preferably 400°C; during the T6 heat treatment, the solution process is preferably 550°C for 2h, and the aging process is preferably 180°C for 12h. Among them, by controlling the T6 heat treatment, part of the stress of the aluminum alloy can be eliminated, thereby improving the shaping and plasticity of the aluminum alloy, so that the aluminum alloy has better deformation ability; it can significantly improve the hardness of the aluminum alloy, so that it has better wear resistance and impact resistance; it can also enhance the corrosion resistance of the aluminum alloy, so that the aluminum alloy has better durability in a humid or corrosive environment, thereby extending its service life.

[0049] It should be noted that SiC p -Al mixed powder is wrapped in aluminum foil to form a 1cm 3The purpose is to facilitate the addition to the aluminum-based melt. When the aluminum-based alloy melt is controlled to be semi-solid, the reinforcement is added by clockwise mechanical stirring, and the stirring time is preferably 10 minutes, followed by heating and counterclockwise stirring for preferably 10 minutes, and the speed of mechanical stirring is preferably ~600rpm. After heating to the liquid melt, an ultrasonic horn is added, and the ultrasonic horn is located 2cm below the liquid surface, the ultrasonic frequency is preferably 20kHz, the power is preferably ~3000w, and the processing time is preferably ~20min.

[0050] It should be noted that the prepared cast composite material is first homogenized, and wire cut and polished according to the size requirements. The homogenization temperature is preferably 500°C, and the time is preferably 12 hours. Then the mold and the cast composite material are preheated to 400°C, the inner wall of the mold is coated with graphite oil at 150°C, and forged, and the forging speed is preferably 0.5mm / s. When the forging reaches the specified height, the upper die is replaced for reverse extrusion, and the reverse extrusion speed is preferably 0.5mm / s. The ratio of the inner diameter of the mold to the diameter of the upper die is preferably 4:3.

[0051] In the second aspect, the present application also provides a micro-nano hybrid SiC prepared by the preparation method described in the first aspect. p Reinforced aluminum matrix composite cylindrical parts. p The reinforced aluminum-based composite cylindrical parts maintain the elongation of the matrix and are endowed with excellent yield strength and tensile strength, thus having excellent mechanical properties.

[0052] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0053] Example 1

[0054] This embodiment provides a micro-nano hybrid SiC p The preparation method of the reinforced aluminum-based composite material cylindrical member specifically comprises:

[0055] according to Figure 1 The preparation process is shown in the preparation process flow chart:

[0056] S101: Micronized SiC with a mass fraction of 2.5wt% p , nano-SiC with a mass fraction of 1.5wt% p Mixed with aluminum powder, micron SiC p 、Nano SiC pThe mass ratio of SiC to aluminum powder is 1:10, and high-energy ball milling is carried out under argon protective atmosphere. The process is as follows: the first stage is material mixing (150rpm, 4h), the second stage is material embedding (220rpm, 10h), the third stage is material welding (330rpm, 6h), clockwise rotation and counterclockwise rotation are alternately carried out every hour, with a rest period of 30min in the middle, to obtain SiC-Al composite particles;

[0057] according to Figure 3 As is known, the appearance of the prepared SiC-Al composite particles can be p It is embedded with aluminum powder to obtain millimeter-sized SiC-Al composite particles;

[0058] S102: Under an argon protective atmosphere, SiC-Al composite particles and aluminum alloy are added to the melting furnace and the temperature is adjusted to 740°C. After the aluminum alloy is melted, the temperature is lowered to 620°C (semi-solid temperature), and then added to the semi-solid aluminum alloy melt by clockwise mechanical stirring. After about 10 minutes, counterclockwise stirring is used for 10 minutes and the melting furnace temperature is increased to 690°C, wherein the stirring speed is about 500-800r / min. Subsequently, the aluminum-based composite material melt is subjected to high-power ultrasonic treatment, the ultrasonic amplitude rod is positioned 2 cm below the liquid surface, the ultrasonic frequency is 20kHz, the power is 3000w, and the treatment time is 20min. The treated aluminum-based composite material melt is cast into a mold preheated to 500°C, and the pressure is maintained at 400MPa for 3 minutes, and homogenized at a temperature of 500°C for 12 hours to obtain a cast SiC p Reinforced aluminum matrix composites;

[0059] Among them, according to Figure 2 The casting mold used is a half-type casting mold with an angle, including a mold base 1, a cover mold 2 and a half mold 3. The cover mold 2 and the half mold 3 are angled for the purpose of demoulding. After the die casting is completed, the casting mold base 1 is removed, the mold is turned 180 degrees, and the middle half mold 3 is pressed out by a press, and then broken into two halves to obtain a cast aluminum-based composite material;

[0060] S103: Cast SiC p The reinforced aluminum matrix composite material was placed in a preheated 400℃ casting mold. At 150℃, the inner wall of the mold was coated with graphite oil and forged at a speed of 0.5mm / s. When the forging reached the specified height, it was kept at 400℃ for 30min, and the upper mold was replaced for reverse extrusion at a speed of 0.5mm / s. Then, T6 heat treatment was performed, with a solution process at 550℃ for 2h and an aging process at 180℃ for 12h to obtain micro-nano hybrid SiC. pReinforced aluminum matrix composite cylindrical parts ((5μm-2.5wt%+50nm-1.5wt%) SiC p / Al-1.6Mg-0.8Si composite cylindrical parts).

[0061] according to Figure 3 The schematic diagram of the continuous hot forging heated reverse extrusion device shown in the figure includes a forging upper die 4, a sleeve die 5, an iron pad 6 in the die, a push rod 7 and a reverse extrusion upper die 8. The forging upper die 4 can transfer the load to the blank to implement the blank forging operation; the sleeve die 5 is fixed to the base of the press with screws and the blank is placed therein; the function of the iron pad 6 is to limit the downward flow of the cast blank when applying high-temperature forging and reverse extrusion; the function of the push rod 7 is to use the push rod to push the cylinder and the iron pad out of the die together after the high-temperature forging and reverse extrusion are completed; after the hot forging is completed, the forging upper die 4 is replaced by the reverse extrusion upper die 8, and its function is to implement hot reverse extrusion to form the cylindrical part. First, the homogenized cast billet is placed in the sleeve mold 5 (it should be noted that the size and height of the billet should be consistent with the sleeve mold), and then the obtained cast material is forged, followed by a back-extrusion operation. After the back-extrusion is completed, the rising push rod 7 pushes the iron pad 6 and the composite material cylindrical part out of the sleeve mold 5, thereby obtaining an aluminum-based composite material cylindrical part.

[0062] At the same time, in order to verify the micro-nano hybrid SiC prepared in the above embodiment p In order to enhance the comprehensive performance of the aluminum-based composite material cylindrical component, the present application provides the following comparative examples for detailed description.

[0063] Comparative Example 1

[0064] The component proportions, preparation operation and process parameters of the B1-aluminum-based composite cylindrical member prepared in the comparative example provided in this application are basically the same as those in Example 1, except that only micron SiC is added to the prepared material in this comparative example. p The aluminum alloy was reinforced to obtain a B1-aluminum-based composite cylindrical member (5μm-4wt% SiC p / Al-1.6Mg-0.8Si composite cylindrical parts).

[0065] Comparative Example 2

[0066] The component proportions, preparation operation and process parameters of the B2-aluminum-based composite cylindrical member prepared in the comparative example provided in this application are basically the same as those in Example 1, except that only nano-SiC is added to the prepared material in this comparative example. p The aluminum alloy was reinforced to obtain a B2-aluminum composite cylindrical member (50nm-1.5wt% SiC p / Al-1.6Mg-0.8Si composite cylindrical parts).

[0067] Comparative Example 3

[0068] The component proportions, preparation operation and process parameters of the B2-aluminum-based composite cylindrical member prepared in the comparative example of the present application are basically the same as those in Example 1, except that no micron SiC is added in the comparative example. p and Nano-SiC p Reinforced materials are used to obtain B3-aluminum-based composite material cylindrical parts (Al-1.6Mg-0.8Si material cylindrical parts).

[0069] In order to verify the appearance of the reinforced aluminum-based composite cylindrical member prepared in the embodiment of the present application, the aluminum-based composite material prepared in the embodiment was tested, and the results were as follows: Figures 5 and 6 As shown. Among them, Figure 5 Cast Al-1.6Mg-0.8Si, 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p / Scanning electron microscope image of Al-1.6Mg-0.8Si reinforced aluminum matrix composite; Figure 6 Al-1.6Mg-0.8Si, 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p Scanning electron microscope image of the cylindrical part of / Al-1.6Mg-0.8Si reinforced aluminum matrix composite material.

[0070] according to Figure 5 It can be seen that the microstructure of the Al-1.6Mg-0.8Si alloy material is dense, no micropores are observed, and the particle distribution is relatively uniform. Figure 5 The grain boundaries of the Al-1.6Mg-0.8Si alloy shown in (a) are discontinuous and the grain size is large. In Figures (bd), it can be seen that the reinforcement particles are mainly distributed along the grain boundaries in the matrix and are distributed relatively evenly, indicating that the early ultrasonic treatment has a certain effect on promoting the uniform distribution of reinforcement particles, and the grains of the composite material have been significantly refined. p The particles have the most obvious effect on the grain refinement of the matrix. This may be due to the fact that during the solidification process, SiC p The particles can act as nucleation sites for grains and promote the nucleation of crystals. On the other hand, during the crystallization process, SiC pParticles can pin grain boundaries and limit the growth of grains. In addition, the acoustic cavitation and acoustic streaming effects generated during ultrasonic treatment can further refine grains. On the one hand, cavitation bubbles will be formed in the metal melt due to the change in sound wave pressure during ultrasonic treatment. The cavitation bubbles will continue to expand until they burst, causing a sharp change in temperature and pressure in the local melt, which will not only change the equilibrium melting point of the material, but also increase the supercooling in certain areas of the melt, promoting nucleation; on the other hand, the vibration of ultrasonic waves will form microscopic eddies and flow layers in the melt. This acoustic streaming effect can strongly stir the melt and hinder the growth of grains, causing grain movement and rearrangement, increasing the number of nuclei, and further enhancing grain refinement.

[0071] according to Figure 6 It can be seen that compared with Al-1.6Mg-0.8Si alloy and 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p The microstructure of the cylindrical parts of the / Al-1.6Mg-0.8Si composite material was found to be p There are many nano-scale precipitates evenly distributed near the particles, and the number of precipitates in the area without particle distribution is small. The size of the precipitates in the composite material is much smaller than that of the Al-1.6Mg-0.8Si alloy and is dispersed. This phenomenon is found in (5μm-2.5wt%+50nm-1.5wt%)SiC p / Al-1.6Mg-0.8Si composites are more obvious, such as Figure 6 (ad) as shown. This may be due to the fact that SiC p The presence of particles leads to an increase in the dislocation density in the composite material. Its high-density dislocation structure provides channels for the diffusion of solute atoms, which is beneficial to the diffusion of solute atoms. In addition, high-density dislocations can serve as nucleation sites for the precipitate phase, thereby accelerating the precipitation and forming a large number of Mg2Si phase-enriched regions.

[0072] In order to verify the micro-nano hybrid SiC prepared in the embodiment of this application p Enhance the mechanical properties of aluminum matrix composite cylindrical parts, and the micro-nano hybrid SiC p The reinforced aluminum matrix composite cylindrical parts were tested and the results were Figures 7 and 8 As shown. Among them, Figure 7 Cast Al-1.6Mg-0.8Si, 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p / Stress-strain curve of Al-1.6Mg-0.8Si composite material; Figure 8 Al-1.6Mg-0.8Si, 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p Engineering stress-strain curve of / Al-1.6Mg-0.8Si reinforced aluminum matrix composite cylindrical parts.

[0073] according to Figure 7 It can be seen that the cast Al-1.6Mg-0.8Si, 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p Engineering stress-strain curve of / Al-1.6Mg-0.8Si composite material. It can be seen from the figure that micro-nano hybrid SiC p The introduction of reinforcement phase has a significant improvement on the performance of the composite material. Compared with Al-1.6Mg-0.8Si alloy, SiC p / Al-Mg-Si composites have significantly improved their strength, among which the micro-nano hybrid SiC p The strengthening effect caused by the particles is significantly higher than the strengthening degree of single-size micron or nano SiC particles. This is because the micro-nano mixed SiC p The introduction of particles refines the grain size and at the same time, SiC p The particles are hard particles, the deformation of the particles and the matrix is ​​not coordinated, and the micro-nano mixed SiC p The introduction of particles will cause dislocation accumulation in the material during the tensile process, resulting in an increase in strength. In addition, it can be found that micron SiC p and Nano-SiC p The introduction of reinforcement phase can not only significantly improve the strength, but also maintain the toughness of the composite material to the greatest extent.

[0074] according to Figure 8 It can be seen that Al-1.6Mg-0.8Si, 5μm-4wt%SiC p / Al-1.6Mg-0.8Si, 50nm-1.5wt%SiC p / Al-1.6Mg-0.8Si, (5μm-2.5wt%+50nm-1.5wt%)SiC p The tensile strength of the cylindrical parts of the Al-1.6Mg-0.8Si reinforced aluminum matrix composites are 168.9MPa, 278.2MPa, 285.3MPa, and 305.3MPa, respectively, and the yield strengths are 78.6MPa, 213.4MPa, 216.8MPa, and 229.4MPa, respectively. Compared with the Al-1.6Mg-0.8Si alloy, SiC p The tensile strength of the Al-Mg-Si composite material increased by 64.7%, 68.9% and 80.8% respectively, and the yield strength increased by 171.5%, 175.8% and 189.8% respectively. This is because the presence of the reinforcing particles will promote the dynamic precipitation of the nanophase as a nucleation site. The presence of a large number of nanophases in the aged aluminum matrix hinders the movement of dislocations and can effectively improve the strength of the matrix. At the same time, the elongation of the composite material can be maintained at 12%-15%.

[0075] The test results of the mechanical properties of the aluminum-based composite cylindrical parts prepared in the examples and comparative examples of the present application are shown in Table 1.

[0076] Table 1 Test results of mechanical properties of aluminum matrix composite cylindrical parts

[0077]

[0078] Therefore, the preparation method provided by the present application is to p 、Nano SiC p After mixing with aluminum powder, high-energy ball milling is performed, and after die-casting with aluminum alloy, continuous forging + reverse extrusion treatment is performed, and then solution aging heat treatment is performed to obtain micro-nano hybrid SiC p Reinforced aluminum-based composite cylindrical parts can improve the dispersion of reinforcements and produce cylindrical parts with excellent mechanical properties.

[0079] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0080] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A micro-nano hybrid SiC p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The method comprises: Micron SiC p 、Nano SiC p After mixing with aluminum powder, high-energy ball milling is performed to obtain SiC-Al composite particles; The SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, and then die-cast and homogenized to obtain the cast SiC p Reinforced aluminum matrix composites; The cast SiC p After the reinforced aluminum matrix composite material is subjected to continuous forging, reverse extrusion and T6 heat treatment, the micro-nano hybrid SiC p Reinforced aluminum matrix composite cylindrical parts.

2. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The micron SiC p The particle size is 0-5 μm, and the added mass fraction is 2.5 wt%.

3. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The nano SiC p The particle size is 0-50nm, and the added mass fraction is 1.5wt%.

4. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The micron SiC p 、Nano SiC p The mass ratio to aluminum powder is 1:

10.

5. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The micron SiC p 、Nano SiC p When the high-energy ball milling treatment is carried out after mixing with aluminum powder, it is carried out in three stages. The first stage is at 150rpm for 4 hours, the second stage is at 220rpm for 10 hours, and the third stage is at 330rpm for 6 hours.

6. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The aluminum alloy is an Al-Mg-Si alloy, and its mass fractions are 97.6% Al, 1.6% Mg, and 0.8% Si.

7. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: When the SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and ultrasonically treated, the ultrasonic frequency is 20 kHz, the power is 3000 W, and the treatment time is 20 min.

8. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: After the SiC-Al composite particles and the aluminum alloy are dissolved at high temperature and subjected to ultrasonic treatment, die casting is performed at a temperature of 500° C., a pressure of 400 MPa, and a time of 3 minutes.

9. The micro-nano hybrid SiC according to claim 1 p A method for preparing a reinforced aluminum-based composite material cylindrical member, characterized in that: The cast SiC p When the reinforced aluminum matrix composite material is continuously forged, the temperature is 400°C; And / or, during the T6 heat treatment, the solution treatment is at 550° C. for 2 h, and the aging treatment is at 180° C. for 12 h.

10. A micro-nano hybrid SiC prepared according to any one of claims 1 to 9 p Reinforced aluminum matrix composite cylindrical parts.

Citation Information

Patent Citations

  • Preparing and processing method of aluminum base composite material large thin-wall shell

    CN103862228A

  • Micro-nano particle reinforced aluminum matrix composite and preparation method thereof

    CN111593218A

  • Micro-nano SiC particle synergistic reinforced aluminum-based composite material and preparation method thereof

    CN117265310A

  • High performance aluminum nanocomposites

    US20150252451A1